The effect of a medical student on community preceptor productivity. Issue 7 (24th January 2022) - Hatfield, Jess; Neal, Gabriel; Isbell, Teresa; Dickey, Danielle
Abstract: Background: Medical students are increasingly being taught in community‐based hospitals and clinics in addition to university‐based health systems, and there is sustained interest in the question of whether medical schools should pay healthcare organizations to allow students to precept to compensate for loss of productivity by preceptors. This study aimed to inform this subject by investigating the effect of medical students on preceptor productivity. Methods: The authors analysed retrospective data on preceptor productivity and time efficiency from 17 outpatient primary care physicians over 7 months and 38, 205 patient visits. Then, the authors surveyed these same physicians to assess how they believe precepting medical students affected their productivity. Results: The retrospective data analysis found that physicians see slightly more patients per half‐day when accompanied by a student. In surveys, these physicians reported the same number of patients seen per half‐day with or without a medical student, but more time spent in clinic with a medical student. They also reported that allowing students to document in the medical record often helped reduce/offset the lengthened workday. Conclusions: Medical students either increase or do not change the number of patients seen per half‐day but can increase preceptor time spent in clinic per day. Generally, physicians accept this increased time for the sake of promoting education and the joy of teaching. These findings can inform medical schools and healthcare organizations when negotiating financial arrangements for preceptorships in community based primary care clinics. Specifically, these findings suggest that medical students precepting do not cost the hospital organization in terms of preceptor productivity. Abstract : Hatfield et al. demonstrate that medical students do not reduce preceptor productivity when measured by number of patients seen per half‐day, raising questions about healthcare organization financial policy.